Interview with Ken Spillman on June 9, 2014 in Australia - Garces-Bacsal, Myra, Ph.D. (Archīum Ateneo, 2014)
Excerpt: Ken Spillman is a multiaward-winning novelist, critic, and editor from Australia. He has been a member of the AFCC’s Board of Advisors since 2010 and of the Programme Committee for the Asian Children’s Writers and Illustrators Conference. He is the author of more than thirty-five books and is a passionate advocate of children’s writing and writers in Australasia. His writing spans the areas of fiction, short fiction, essays, history, poetry, travel, and sports writing. He has also done multiple school visits to school children around Australia, China, India, Malaysia, Oman, the Philippines, Indonesia, and Singapore. His latest picture book, The Circle, is a multicultural narrative that explores what it means to be different and how one navigates his or her way in an environment filled with suspicion, doubt, and fear. It also portrays a vision of how one may be able to let go of such fears and the quiet promise of what a truly “inclusive” environment looks like in this “dwindling forest” of a world that we live in now.